Teknologi Digital dalam Perspektif Seni Visual - Widyatmoko , R. Nanang (Universitas Widya Mataram, 2025)
The paradigm of visual art mediums, whether in the context of three-dimensional or two-dimensional materials, generally tends to trace lines, planes, spaces, colors, textures, light (dark and light), and shapes. On the other hand, art also includes movement (dance) and sound (music). However, works of art are not always boxed in by type. Each can complement each other in a collaboration that leads to a creative, narrative and participatory art form. Meanwhile, digital technology has characteristics that are logical, coherent numerical representation, systematic modularity, automatic, analytical, variability and transconding (the relationship between computing and daily cultural life). Digital technology is closely related to the media, therefore the media continues to develop along with the advancement of digital technology. The development of digital technology produces new media (digital) as a development of old media (analog). The latest breakthrough in the world of visual art that combines elements of conventional art with digital technology. Thus, visual art develops in accordance with the development of media technology considering that art is often manifested through visual media. Conventional art developed in combination with digital technology is called new media art. Forms of new media art can be identified in video media, video installation, video art, video games, photography, digital print, digital painting, digital imaging, 2D animation, 3D animation, web-art, or other interactive art.